2011
DOI: 10.3390/md9091440
|View full text |Cite
|
Sign up to set email alerts
|

Production of Bioactive Secondary Metabolites by Marine Vibrionaceae

Abstract: Bacteria belonging to the Vibrionaceae family are widespread in the marine environment. Today, 128 species of vibrios are known. Several of them are infamous for their pathogenicity or symbiotic relationships. Despite their ability to interact with eukaryotes, the vibrios are greatly underexplored for their ability to produce bioactive secondary metabolites and studies have been limited to only a few species. Most of the compounds isolated from vibrios so far are non-ribosomal peptides or hybrids thereof, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(112 citation statements)
references
References 143 publications
3
108
0
1
Order By: Relevance
“…Bacteria belonging to the genus Vibrio are well recognized for their symbiotic relationships, pathogenicity, and the production of bioactive secondary metabolites (61)(62)(63)(64). Opisthobranchs are known to secrete metabolites in their mucus as a defense mechanism (41).…”
Section: Discussionmentioning
confidence: 99%
“…Bacteria belonging to the genus Vibrio are well recognized for their symbiotic relationships, pathogenicity, and the production of bioactive secondary metabolites (61)(62)(63)(64). Opisthobranchs are known to secrete metabolites in their mucus as a defense mechanism (41).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Oliva et al (44) showed that the yeasts Saccharomyces cerevisiae and Candida kefyr are not affected by holomycin. P. halotolerans produces two depsipeptides called solonamide A and B, which have a chemical structure similar to unnarmicins (45). Unnarmicins have been identified in a Photobacterium strain (46) and inhibit fungal ATP binding cassette transporters (ABC), which are involved in drug resistance (47).…”
Section: Discussionmentioning
confidence: 99%
“…There are two cyclization domains, followed by an adenylation domain, a condensation domain, a peptidyl carrier protein (PCP) domain, and a second condensation domain (46). This assembly process on a NRPS with distinct, modular domains is characteristic of bacterial catechol siderophores and other secondary metabolites, including antibiotics, and has been described in detail for E. coli and other species (52)(53)(54). The domain structure of the NRPSs has facilitated the evolution of a large family of distinct siderophores with variations in the peptide backbones, chelating moieties, or other modifications.…”
Section: Transport Of Iron Complexesmentioning
confidence: 99%